Take -home naloxone rescue kits following heroin overdose in the emergency department to prevent opioid overdose related repeat emergency department visits, hospitalization and death- a pilot study - Joan Papp; Mayur Vallabhaneni; Ariel Morales; Jon W. Schrock (BMC, 2019)
Abstract Background Opioid overdoses are at an epidemic in the United States causing the deaths of thousands each year. Project DAWN (Deaths Avoided with Naloxone) is an opioid overdose education and naloxone distribution program in Ohio that distributes naloxone rescue kits at clinics and in the emergency departments of a single hospital system. Methods We performed a retrospective analytic cohort study comparing heroin overdose survivors who presented to the emergency department and were subsequently discharged. We compared those who received a naloxone rescue kit at discharge with those who did not. Our composite outcome was repeat opioid overdose related emergency department visit(s), hospitalization and death at 0-3 months and at 3-6 months following emergency department overdose. Heroin overdose encounters were identified by ICD- 9 or 10 codes and data was abstracted from the electronic medical record for emergency department patients who presented for heroin overdose and were discharged over a 31- month period between 2013 and 2016. Patients were excluded for previous naloxone access, incarceration, suicidal ideation, admission to the hospital or death from acute overdose on initial emergency department presentation. Data was analyzed with the Chi- square statistical test. Results We identified 291emergency department heroin overdose encounters by ICD-9 or 10 codes and were analyzed. A total of 71% of heroin overdose survivors received a naloxone rescue kit at emergency department discharge. Between the patients who did not receive a naloxone rescue kit at discharge, no overdose deaths occurred and 10.8% reached the composite outcome. Of the patients who received a naloxone rescue kit, 14.4% reached the composite endpoint and 7 opioid overdose deaths occurred in this cohort. No difference in mortality at 3 or 6 months was detected, p = 0.15 and 0.36 respectively. No difference in the composite outcome was detected at 3 or 6 months either, p = 0.9 and 0.99 respectively. Conclusions Of our emergency department patients receiving a naloxone rescue kit we did not find a benefit in the reduction of repeat emergency department visits hospitalizations, or deaths following a non-fatal heroin overdose.